Computation accuracy of electromagnetic wave propagation over irregular terrain - Schejbal, Vladimír (Univerzita Pardubice, 2001)
The computer model and computation accuracy for propagation over irregular terrain are presented. Special attention is paid to computation accuracy considering integration and step size. The effect of integration step selection for various wavelengths and terrain profiles is demonstrated using numerical simulations.
Keywords: šíření vln; terén; výpočty; přesnost; počítačová simulace; Modelování; optika